Acremonium variecolor strain 130360 VS Trichoderma harzianum STRAIN MGQ2 IN BIOCONTROL: AN OVERVIEW OF FUNGAL ANTAGONIST APPLIED AGAINST FUNGAL PATHOGEN Fusarium oxysporum, A CAUSE OF MOLER’S DISEASE IN SHALLOT - Gunawan Sutio; Rani Maharani; Nur Afifah Azzahra (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
One of the common diseases of shallot is moler disease, caused by Fusarium oxysporum. This disease causes some damage to the plant. The attack mechanism of Fusarium oxysporum is by penetrating, colonizing, and multiplying in the root area, then parasitizing and inhibiting the process of carrying water to whole parts of the plant. Biological control of moler diseases using fungal antagonist has developed considerably in recent years. Fungal antagonists play a significant role in controlling plant pathogens and moler diseases caused by Fusarium oxysporum, such as Trichoderma harzianum and Acremonium variecolor. A series of experiments in field conducted to assess the comparison of ability between Trichoderma harzianum strain MGQ2 and Acremonium variecolor strain 130360 in effectively controling moler in shallot.